Cell perturbation screens for target identification by RNAi - Demir, Kubilay; Boutros, Michael (Bioinformatics and Drug Discovery, 2012)
Over the last decade, cell-based screening has become a powerful method in target identification and plays an important role both in basic research and drug discovery. The availability of whole genome sequences and improvements in cell-based screening techniques opened new avenues for high-throughput experiments. Large libraries of RNA interference reagents available for many organisms allow the dissection of broad spectrum of cellular processes. Here, we describe the current state of the large-scale phenotype screening with a focus on cell-based screens. We underline the importance and provide details of screen design, scalability, performance, data analysis, and hit prioritization. Similar to classical high-throughput in vitro screens with defined-target approaches in the past, cell-based screens depend on a successful establishment of robust phenotypic assays, the ability to quantitatively measure phenotypic changes and bioinformatics methods for data analysis, integration, and interpretation.